High-Frequency Spinal Cord Stimulation at 10 kHz for the Treatment of Combined Neck and Arm Pain: Results From a Prospective Multicenter Study - Amirdelfan, Kasra; Vallejo, Ricardo; Benyamin, Ramsin; Yu, Cong; Yang, Thomas; Bundschu, Richard; Yearwood, Thomas L; Sitzman, B Todd; Gliner, Bradford; Subbaroyan, Jeyakumar; Rotte, Anand; Caraway, David (Neurosurgery, 2020)
Abstract BACKGROUND Intractable neck and upper limb pain has historically been challenging to treat with conventional spinal cord stimulation (SCS) being limited by obtaining effective paresthesia coverage. OBJECTIVE To assess the safety and effectiveness of the 10-kHz SCS system, a paresthesia-independent therapy, in the treatment of neck and upper limb pain. METHODS Subjects with chronic, intractable neck and/or upper limb pain of ≥5 cm (on a 0-10 cm visual analog scale [VAS]) were enrolled in 6 US centers following an investigational device exemption from the Food and Drug Administration (FDA) and institutional review board approval. Each subject was implanted with 2 epidural leads spanning C2-C6 vertebral bodies. Subjects with successful trial stimulation were implanted with a Senza® system (Nevro Corp) and included in the evaluation of the primary safety and effectiveness endpoints. RESULTS In the per protocol population, the primary endpoint (≥50% pain relief at 3 mo) was achieved in 86.7% (n = 39/45) subjects. Compared to baseline, subjects reported a significant reduction (P < .001) in their mean (± standard error of the mean) VAS scores at 12-mo assessment for neck pain (7.6 ± 0.2 cm, n = 42 vs 1.5 ± 0.3 cm, n = 37) and upper limb pain (7.1 ± 0.3 cm, n = 24 vs 1.0 ± 0.2 cm, n = 20). At 12-mo assessment, 89.2% of subjects with neck pain and 95.0% with upper limb pain had ≥50% pain relief from baseline, 95.0% reported to be “satisfied/very satisfied” and 30.0% either eliminated or reduced their opioid intake. CONCLUSION In conclusion, 10-kHz SCS can treat intractable neck and upper limb pain with stable long-term outcomes.